THE ASSESSMENT OF HEAVY METALS POLLUTION OF WATER BODIES AND SOIL IN THE ZONE OF ECOLOGICAL DISASTER (CITY KARABASH) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The report gives intermediate results of research carried out as the start of the INTAS Project “Strategy development for long term pollution control in regions of extreme environmental risk (ENVRISK)” The work on the project is a logical continuation of the research by project INCO-Copernicus TOXICAL (Contract No ICA2- CT2001-0016) [Ref. to preceding Conference] [14]. The major goal of the work is to elaborate a strategy and methods of pollution assessment and monitoring of Argazinskoye water storage basin, which is a reserve of drinking water supply for he city of Chelyabinsk in order to take steps for mitigating the health risk of the population of the region. The Russian project participants of the United Institute of Physics of the Earth, Russian Academy of Sciences, were presented with the following tasks. ? Grading and summing up the available data on the geological and tectonic structure and heavy metal pollution of the region; ? To substantiate field observation stations network and points of sampling of soil, biomass and surface water for laboratory analysis of heavy metal content; ? Rating stations of monitoring surface water pollution by neutron logging in relation to ecological conditions of the region; ? To obtain data on areal distribution of heavy metals pollution of soils, underground water and biomass; ? To elaborate a model of major pollutants spreading with surface runoff and hydrology system of the region on the basis of GIS technologies; ? To work out recommendations for local authorities to minimize health risk of the population. Currently a map of sampling has been made, sampling techniques have been elaborated in compliance with effective norms (GOST), samples processing and partial chemical analysis have been carried out. Some results of the research are given below.